2021
DOI: 10.1016/j.ajog.2020.12.1021
|View full text |Cite
|
Sign up to set email alerts
|

996 Impact of COVID-19 on obstetrical outcomes at a single academic medical center

Abstract: whereas at week 8, 56% reported no change in their meal enjoyment when following carbohydrate-last food order. CONCLUSION: The majority of patients adhered to carbohydrate-last food order intervention, with a neutral effect on meal enjoyment over time. Food order appears to be a feasible nutritional strategy in patients with GDM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Another study, which provided insufficient data to be included in this metaanalysis, reported that the risk of preeclampsia was significantly higher during the COVID-19 pandemic than before the pandemic (RR, 1.53; 95% CI, 1.24e1.90 when compared to the 2018 preeclampsia rate; RR, 1.25; 95% CI, 1.02e1.52 when compared to the 2019 preeclampsia rate). 168 These data support the findings of our study.…”
Section: Strengths and Limitationssupporting
confidence: 90%
“…Another study, which provided insufficient data to be included in this metaanalysis, reported that the risk of preeclampsia was significantly higher during the COVID-19 pandemic than before the pandemic (RR, 1.53; 95% CI, 1.24e1.90 when compared to the 2018 preeclampsia rate; RR, 1.25; 95% CI, 1.02e1.52 when compared to the 2019 preeclampsia rate). 168 These data support the findings of our study.…”
Section: Strengths and Limitationssupporting
confidence: 90%